The effect of high intensity pulsed electric field on the coconut milk - Zainol, Mohd. Zaifulrizal (2010)
In recent years, several techniques for the preservation of foods have appeared as alternative to the traditional procedures such as thermal, chemical and so on. The aim of these new techniques is to better preserve the original of foods than the classical techniques. Nonthermal food processing with PEF technology has been of growing interest as an important research in the food industry. PEF not only inhibits pathogenic and spoilage microorganisms but also results in the retention of flavor, aroma, nutrients and colour of foods. Apart from provides the fundamental information about PEF food processing, experiments have been carried out to investigate the effect of high intensity pulsed electric field on the shelf life of coconut milk. The treatment chamber in a laboratory-size prototype consists of two parallel stainless metal plates with the separation of 1.5 cm was designed and constructed. A double blumlein pulse generator was constructed using a coaxial cable which is capable of providing output voltage up 2 times from power supply and produces square-wave pulse width of 100 ns.